Penerapan Project Based Learning Pada Materi Asam Basa Untuk Meningkatkan Hasil Belajar Siswa Di SMA Negeri I Tagulandang - Rauhe, Gilliant; Tuerah, Jeanne; Waworuntu, Freetje (Oxygenius: Journal Of Chemistry Education, 2025)
This research was conducted with the aim of determining the effect of implementing the PjBL model in improving the learning outcomes of class XII A students at SMA Negeri 1 Tagulandang. This research was carried out in two learning cycles and the learning stages consisted of determining basic questions, preparing a project design, creating an activity schedule, monitoring the distribution of student performance and evaluating experience. The research objects were class XII A students of SMA Negeri 1 Tagulandang for the odd semester 2024/2025 academic year, totaling 32 students. Data collection techniques include observation, learning results tests and documentation. The data analysis technique includes test results data. The results show that the level of student learning completion has increased. In cycle I, the percentage of completeness was obtained, namely 56.20% with the highest score of 88. Meanwhile, in cycle II, the percentage of completeness was obtained, namely 90.62%, with the highest score being 93. Based on the research results, the application of the PjBL model improved student learning outcomes.